The Challenges of Measuring Human Performance in Complex Operational Environments. (September 2016) - Savage-Knepshield, Pam; Hullinger, David; Lund, Rachael; Manning, Carol; Pierce, Linda; Seely, Owen; Thomas, Jeffrey
A panel of experienced human factors practitioners and researchers discusses the challenges encountered when measuring and quantifying human performance on the job and during system design and development. The panel, comprised of government/military researchers with expertise in human factors engineering, human systems integration, research psychology, industrial/organizational psychology, physics, systems engineering, and mechanical engineering, focuses not only on the challenges they have encountered, but also on the underlying human performance measurement issues and various approaches they have taken to address them. Understanding, measuring, evaluating and predicting factors that influence human performance is not only critical for the design of effective systems and programs of instruction, but also for overall job performance and mission effectiveness. Panelists will discuss critical factors and insights that are generalizable across a wide range of products and industry sectors as well as those that warrant further investigation.